Frozen sections compared with paraffin-embedded sections: A retrospective veterinary autopsy study - Stern, Adam W. (Brazilian Journal of Veterinary Pathology, 2020)
Histologic examination of tissues collected at autopsy are typically prepared using conventional methods (formalin fixed, paraffin‐embedded tissue). In this study, twenty-five tissue specimens from twelve animals were collected at autopsy and examined using the frozen section technique. Of the 25 specimens examined, an accurate and specific diagnosis was obtained in 21 specimens; the pathologic process was correctly identified, but a specific diagnosis was not obtained in 1 specimen; the diagnosis was missed in 2 specimens, and in 1 specimen the diagnosis was deferred. Of the two incorrect diagnoses, one was due to a sampling error and one was due to an interpretation error. Overall, the use of postmortem frozen sections allowed for complete agreement with conventional methods in 21 specimens (84%) and the results from this study support the use of frozen section examination of tissue samples collected postmortem.